"I'M NOT A TARGET MARKET": Power asymmetries in market segmentation. (October 2016) - Kannisto, Päivi
Abstract: This study examines the underlying assumptions, values and norms of market segmentation and their effects. While segmentation aims to support the firm's overall value proposition, it may also constrain aims to be more customer-centric. In the analysis, the focus is on subtle and often invisible forms of micro-power that are practised through everyday business actions. Although the study is conceptual, it is practice-oriented, providing managers with a checklist of questions that can be used for assessing the firm's power relations. Transparency, value co-creation, individualised segmentation, and empathy are suggested for redressing unfavourable power differentials, and for building long-term customer relationships. Highlights: The study examines power asymmetries created by market segmentation. These self-created obstacles may constrain businesses from reaching their aims. The study presents a checklist that can be used for assessing the firm's power relations. Transparency, value co-creation, communities, individualisation, and empathy are suggested.